A modification of the FRAD model for personal names in non-Roman languages. Issue 5 (14th September 2015) - Kimura, Maiko
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to propose a modification of the Functional Requirements for Authority Data (FRAD) model to accommodate names in non-Roman languages with diverse writing systems. Design/methodology/approach – The model modifies and clarifies the attributes and relationships regarding non-Roman languages of the current FRAD model, based on the definitions of transliteration, transcription, and Romanization in ISO 5127:2001. The modified model overcomes the problems inherent in the current FRAD model when handling writing systems in non-Roman languages. Findings – The proposed model clearly shows the hierarchy of Controlled Access Points (CAPs). CAPs are either based directly on names or derived from other CAPs. For name or person identification, a CAP and its derivations should be treated as a set. The proposed model also resolves ambiguity in the definition of the word transliteration in the current FRAD model. Originality/value – By establishing new relationships and amending the attributes of the FRAD model, the proposed model better expresses personal names in non-Roman languages as well as names in western languages. It also organizes complex writing systems of non-Roman languages. The proposed model could lead to an improved format for authority data and will facilitate international sharing of data.